Analysis of the influence of iron source and its occurrence state on the color of celadon glaze. Issue 13 (1st July 2022) - Liu, Pengju; Wang, Fen; Luo, Hongjie; Zhu, Jianfeng; Shi, Pei; Hao, Yaorui; Feng, Bing
Abstract: Using different iron sources of industrial iron oxide, loess, slag, and golden soil, iron elements were introduced into the formula respectively, and celadon samples were prepared in a reducing atmosphere. To reveal the influence of iron source on glaze color, the celadon samples were analyzed by Spectrophotometer, X-ray fluorescence spectroscopy, X-ray diffractometer, scanning electron microscope, and X-ray photoelectron spectrometer. The results show that the glaze color of the samples is quite different, samples using iron oxide and golden soil as iron source raw materials are sky-green, the loess sample is olive green, and the slag sample is similar to the bean green. There are many quartz crystals in the glaze of iron oxide samples, and the turbidity is high. The liquid-liquid phase separation size close to the quartz crystal is large, and far away from the crystal is small. Industrial iron oxide is the easiest to reduce, followed by goethite in golden soil, and reduction of hematite in slag and the iron in loess in the form of isomorphic is successively more difficult. The difference in the form of occurrence of iron is the most essential factor that causes the difference in glaze color.